2008
DOI: 10.1007/s10654-008-9272-0
|View full text |Cite
|
Sign up to set email alerts
|

Does population mixing measure infectious exposure in children at the community level?

Abstract: Epidemiological studies focusing on the etiology of childhood chronic diseases have used population mixing as a proxy for the level of infection circulating in a community. We compared different measures of population mixing (based on residential migration and commuting) and other demographic variables, derived from the United Kingdom Census, with hospital inpatient data on infections from two Government Office Regions in England (Eastern and the West Midlands) to inform the development of an infectious diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…The coefficient values of income, education, and population density are −0.6951 ( p -value < 0.01), −0.0160 ( p -value > 0.05), and 0.1093 ( p -value > 0.05), respectively, revealing that a 10-unit increase in income results in a 0.6951% decrease in neonatal deaths because of acute respiratory infection in selected Asian countries. These results are in line with the previous studies available in literature [12,35,36,37,38].…”
Section: Resultssupporting
confidence: 93%
“…The coefficient values of income, education, and population density are −0.6951 ( p -value < 0.01), −0.0160 ( p -value > 0.05), and 0.1093 ( p -value > 0.05), respectively, revealing that a 10-unit increase in income results in a 0.6951% decrease in neonatal deaths because of acute respiratory infection in selected Asian countries. These results are in line with the previous studies available in literature [12,35,36,37,38].…”
Section: Resultssupporting
confidence: 93%
“…To our knowledge, no other study has investigated neighbourhood child density as a potential proxy for exposure to infections. An ecologic study from the UK found increased higher hospital admission rates for infections among children 0 to 14 years of age who lived in wards with high population density [ 9 ]. A number of studies have explored the transmission of infections in relation to patterns of social contact.…”
Section: Discussionmentioning
confidence: 99%
“…While it is known that children attending day-care centres [ 6 , 7 ] or children with older siblings [ 8 ] tend to have more infections, evidence of associations between population density and children’s exposure to infections is limited. To our knowledge, only one previous ecologic study from the UK has investigated this and found an increase in hospital admissions for infection in children living in areas with high population density [ 9 ]. While day-care attendance can only be assessed through active participation of parents (interview or questionnaires), population density and birth order are more readily available from routine data.…”
Section: Introductionmentioning
confidence: 99%
“…Higher levels of population mixing associated with a reduced risk of CNS tumours may have occurred through a protective effect for exposure to infection, since population mixing has been shown to be a reasonable proxy for infectious exposure [36]. One possible mechanism may involve immune system priming in early life by exposure to a wide range and high volume of infection, and may be important in terms of protection against later development of CNS tumours among TYAs.…”
Section: Discussionmentioning
confidence: 99%
“…As previously stated, use of population mixing has been shown to be a reliable proxy measure for infection in ecological study designs [36]. …”
Section: Discussionmentioning
confidence: 99%